2020
DOI: 10.3390/biom10040607
|View full text |Cite
|
Sign up to set email alerts
|

Negative Roles of Strigolactone-Related SMXL6, 7 and 8 Proteins in Drought Resistance in Arabidopsis

Abstract: Previous investigations have shown that the SUPPRESSORS OF MAX2 1-LIKE6, 7 and 8 (SMXL6, 7 and 8) proteins redundantly repress strigolactone (SL) signaling in plant growth and development. Recently, a growing body of evidence indicated that SLs positively regulate plant drought resistance through functional analyses of genes involved in SL biosynthesis and positive regulation of SL signaling. However, the functions of the SL-signaling negative regulators SMXL6, 7 and 8 in drought resistance and the associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Generally, when facing with detrimental environmental stresses, plants initiate a wide range of enzymatic and non-enzymatic antioxidants to scavenge excess free radicals, including ROS [ 54 , 78 , 79 ]. The polyphenolic compounds are the central components of non-enzymatic antioxidants [ 54 ]; and thus, promotion of their biosynthesis is a defense strategy against adverse environmental conditions [ 76 , 80 , 81 ]. Consistent with the results of transcriptome analysis, results of RT-qPCR analysis also verified up-regulation of several key flavonoid, phenylpropanoid, and anthocyanin biosyntheses-related genes, especially OvFLS , in the TD/MH comparison ( Figure 11 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, when facing with detrimental environmental stresses, plants initiate a wide range of enzymatic and non-enzymatic antioxidants to scavenge excess free radicals, including ROS [ 54 , 78 , 79 ]. The polyphenolic compounds are the central components of non-enzymatic antioxidants [ 54 ]; and thus, promotion of their biosynthesis is a defense strategy against adverse environmental conditions [ 76 , 80 , 81 ]. Consistent with the results of transcriptome analysis, results of RT-qPCR analysis also verified up-regulation of several key flavonoid, phenylpropanoid, and anthocyanin biosyntheses-related genes, especially OvFLS , in the TD/MH comparison ( Figure 11 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that triflumizole inhibits SL biosynthesis in rice by inhibiting Os900 activity. As SLs play an important role in plant development and resistance of environmental stress [ 1 , 39 ], triflumizole may be useful tool for analyzing the influence of SL biosynthesis inhibition and controlling the damage of root parasitic plants. However, because the dwarf phenotype is a side effect of triflumizole, a structure-activity relationship study using triflumizole as the lead compound will be necessary in the near future to attempt to reduce this side effect and conclusively establish triflumizole derivatives as a specific SL biosynthesis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the activities of SOD, GPOX, PPO, APX and CAT enzymes increased in roots and leaves of both chickpea varieties exposed to RD treatments (Figure 5A-J). However, despite the increased activities of these antioxidant enzymes upon RD (Figure 5A-J Secondary metabolites, including TPhs and flavonoids, are known to be important antioxidant compounds for scavenging ROS in stressed plants (Gao et al 2020;Li et al, 2020;Ma et al 2014;Okunlola et al 2017;Patel et al 2020;Rahman et al 2021). In the present study, we detected a large increase in the contents of TPhs and flavonoids in the roots and leaves of both chickpea varieties in response to RD-induced over-production of ROS (Figure 4C-J).…”
Section: Leaves Rootsmentioning
confidence: 99%